PENERAPAN TEORI JEROLD E. KEMP BERBASIS METODE PQ4R UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS X TSM PADA MATERI POKOK PROGRAM LINEAR DI SMKN 1 GERUNG TAHUN PELAJARAN 2012/2013 - FATMAWATI, DIAH (IKIP Mataram, 2013)
Mathematics learning in SMKN 1 Gerung considered by some students is a difficult and tedious lesson. Learning is still teacher-centered and leads to reduced activity and enthusiasm for students in learning. The purpose of this study is to improve student activity and achievement using Jerold E. Kemp-based PQ4R method on the subject matter of linear program of students of class X-TSM SMKN 1 Gerung academic year 2012/2013. This study was conducted using classroom action research (PTK). The number of subjects in this study was 24 people. Observation data of student and teacher activity is qualitative and student learning evaluation is quantitative data. The instruments used are RPP, student and teacher observation sheets, LKS, and evaluation tests. The results showed that there is an increase in student activity and achievement from first to second cycle. Increased student learning activities can be seen in the results of the first cycle of observation I (the category is quite active) and at the second meeting (active category). In cycle II at session I and II (active category). The completeness of learning cycle I is 56.52%, because in the first cycle of classical completeness has not met the required ≥85% of students who got the value of ≥75 then the research continued into the second cycle. Finally, through the improvements obtained classical completeness in the second cycle reached 87.50%. It can be concluded that the application of Jerold E. Kemp theory based on PQ4R method can increase student activity and achievement.